2019
DOI: 10.1021/acs.jmedchem.9b00644
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Albiziabioside A Conjugated with Pyruvate Dehydrogenase Kinase Inhibitor Dichloroacetate To Induce Apoptosis-Ferroptosis-M2-TAMs Polarization for Combined Cancer Therapy

Abstract: The reprogramming of energy metabolism is considered to be one of the main characteristics of cancer. The development of therapeutic agents targeting glycolysis to alter aberrant glucose metabolism and restore oxidative phosphorylation has emerged as an effective approach for cancer therapy. In this way, we have developed a conjugate AlbA-DCA, which can induce a marked increase in intracellular ROS and alleviate the accumulation of lactic acid in TME. Meanwhile, AlbA-DCA selectively kills cancer cells and exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 43 publications
(64 reference statements)
0
42
0
Order By: Relevance
“…The generated hydroxyl radicals subsequently induce lethal ferroptosis to tumor cells ( 54 ). A novel conjugate AlbA-DCA was developed via inhibition of the GPX4 pathway and elimination of procarcinogenic M2-TAMs to suppress tumor progression in breast cancer ( 53 ) ( Table 2 and Figure 3 ). Another study reported that M1 phagocytes exert higher ferroptosis resistance than M2 phagocytes, but that inducible nitric oxide synthase (iNOS)/NO-enrichment of phagocytes can modulate the sensibility of phagocytes to ferroptosis.…”
Section: Ferroptosis In Tumor Microenvironments and Immunotherapy Of mentioning
confidence: 99%
“…The generated hydroxyl radicals subsequently induce lethal ferroptosis to tumor cells ( 54 ). A novel conjugate AlbA-DCA was developed via inhibition of the GPX4 pathway and elimination of procarcinogenic M2-TAMs to suppress tumor progression in breast cancer ( 53 ) ( Table 2 and Figure 3 ). Another study reported that M1 phagocytes exert higher ferroptosis resistance than M2 phagocytes, but that inducible nitric oxide synthase (iNOS)/NO-enrichment of phagocytes can modulate the sensibility of phagocytes to ferroptosis.…”
Section: Ferroptosis In Tumor Microenvironments and Immunotherapy Of mentioning
confidence: 99%
“…Synthetic oleanolic saponins (Figure 2) have been evaluated on their antitumor [14,18,21,[29][30][31][32][33][34][35][36][37], anti-Alzheimer [38], antiviral [39,40], antiglucosidase [41], immunomodulating [42], and detoxification [43] activities (Table 1). Yang and co-workers reported a series of structures derivatized from potent antitumor Pulsatilla saponins, hederacolchiside A and D, elucidating the selectivity between the antitumor activity and hemolytic toxicity of compounds.…”
Section: Oleanolic Acidmentioning
confidence: 99%
“…To further improve antitumor efficacy, a secondary amine moiety of AlbA was conjugated with dichloroacetate (6), a pyruvate dehydrogenase kinase inhibitor, to disrupt glycolysis pathway in cells, leading to increased intracellular reactive oxygen species (ROS) and decreased accumulation of lactic acid in the tumor microenvironment. The cancer cell death was induced by caspase-dependent pathway activation, GPX4 pathway suppression, and lipid peroxidation accumulation, which can be summarized into apoptosis-ferroptosis-M2-TAM polarization [30]. Sun and co-workers constructed the synthesis method of four naturally occurring oleanolic saponins, revealing that monodesmosidic saponin exhibited higher antitumor cytotoxicity than bidesmosidic saponin [29].…”
Section: Oleanolic Acidmentioning
confidence: 99%
“…It was reported that natural products generated ROS to promote cancer cell apoptosis (40)(41)(42)(43)(44), and in the current study a rescue experiment was performed to reveal the role of ROS in PPII inhibition. With a test of concentration gradient of N-acetyl-L-cysteine (NAC, a ROS scavenger), in U87 cells the PPII inhibition was reversed from 4 mg/mL NAC (Figure 5A), and in U251 cells the PPII inhibition was reversed from 8 mg/mL NAC by CCK-8 assays (Figure 5B).…”
Section: Ros Mediated Ppii Inhibition In U87 and U251 Cells Via Bax/cyt-cmentioning
confidence: 92%